Answer:
<u>x = -4/3</u>
Step-by-step explanation:
3x + 4 = 0
3x = -4
<u>x = -4/3</u>
Option A is the correct answer, y = x + 2
y - 3 = x-1
If you bring the 3 to the R.H.S, it becomes y = x + 2
If you substitute the values,
3 = 1 + 2
3 = 3
Thus, e equation is correct
Answer:
trucks: 8, cars: 18
Step-by-step explanation:
Answer:
Associative Property of Multiplication
Step-by-step explanation:
We are given three numbers-a,b,c.
We are given the property (ab)c = a(bc)
This implies that on the left hand side we first multiply a and b and then multiply the result by c. On the right side of the equation, we first multiply b and c and multiply a with the product of b and c.
As per the given property, the result in both the cases is the same.
This signifies the associative property of multiplication where the result is independent of the order of operation.
Pemdas? OK so how I would remember it by is "Please Excuse My Dear Aunt Sally"
So.. Parenthesis, Exponent(s), Multiplication, Division, Addition, Subtraction..
Example~~~~~
(
![3^2}](https://tex.z-dn.net/?f=%203%5E2%7D%20)
+ 4) ×12÷4 - 1= ? so first do parenthesis and then the exponents then add it to 4 and the divide 12 and 4 and then subtract 1 which is 2.. Then after take two and 13 and multiply which is 26~
Hope this helps! :)